Factors affecting colostrum quality in Australian pasture‐based dairy herds. Issue 11 (27th October 2017) - Chuck, GM; Mansell, PD; Stevenson, MA; Izzo, MM
Abstract : Objective: The aim of this study was to identify factors affecting colostrum quality in dairy cattle. Methods: Colostrum samples were collected from lactating dairy cows (n = 990) from nine commercial dairy herds in south‐west Victoria. Colostrum quality was measured using an optical Brix refractometer. Cow‐level factors thought to influence colostrum quality included season of calving, dam breed and age, volume of first‐milking colostrum produced and whether the dam leaked colostrum prior to calving. Multivariable logistic regression was used to quantify the association between each cow‐level factor and whether or not colostrum was assessed to be of poor quality. Results: Cows older than 5 years of age were less likely to have poor‐quality colostrum compared with primiparous heifers (odds ratio (OR) 0.62, 95% confidence interval (CI) 0.11–0.89, P = 0.009). The odds of having poor‐quality colostrum was increased in cows and primiparous heifers that leaked colostrum prior to calving (OR 2.06, 95% CI, 1.33–3.17, P = 0.001). Cows and primiparous heifers that produced ≥ 8.5 L of colostrum were 1.76 times as likely to have poor‐quality colostrum as individuals that produced < 8.5 L (95% CI, 1.10–2.82, P = 0.018). Visual assessment of colostrum by the herd manager was moderately correlated with colostrum quality, with 69% of poor‐quality samples being correctly classified. Conclusion: Although this study identified factors that increase the risk of poor‐quality colostrum, we concluded that objective assessment using a Brix refractometer is a more reliable means of assessing colostrum quality.